Efficacy of antiglide plate in vertical shear fractures of medial malleolus due to supination adduction injury around ankle: a prospective clinical study - Arora, Kamal Kumar; Kapila, Rajesh; Chaudhary, Priti; Singh, Raminder; Kapila, Sarika (International Surgery Journal, 2021)
Background: Ankle fractures represent 10% of all fractures with an incidence of around 137/100000 population per year, making these the second most common lower limb fractures after hip fractures. Increasing age, obesity and alcohol abuse are the major causal factors for the fractures around the ankle joint. These are typically low energy injuries with the majority occurring due to simple falls or sport. The aim was to open reduction and internal fixation of these with an antiglide plate. Methods: The present prospective study was carried out at government medical college Amritsar, Punjab in 25 patients of same demographic profile, March 2018 to December 2020 after having the clearance of ethical committee. All the patients after careful assessment of the injury both clinically (pain, swelling, deformity, any blisters) and radiologically (type of fracture, that is, vertical shear fracture of medial malleolus) were internally fixed under spinal anesthesia, with an antiglide plate after reduction of the fracture fragments. Results: The results were assessed accordance with Olerud-Molander ankle score (OMAS). We achieved excellent to good results with an average OMAS score of 80/100 in the present study. Conclusions: The open reduction and internal fixation of vertical shear fractures of medial malleolus with an antiglide plate is an effective way of management of these fractures. It ensures maximum stability and more so safeguards against loss of reduction or the implant failure under axial loading and at the same time ensures the timely union of such fractures without any significant complications.